Investigating mechanisms of transcriptional interference in Schizosaccharomyces pombe - Watts, B (2015)
Eukaryotic cells transcribe a vast array of non-coding RNAs, most of which have not been assigned a functional role. The work presented here reveals a novel mechanism of transcriptional repression that is mediated by the non-coding RNA prt (pho1-repressing transcript). The prt transcript is shown to recruit a histone deacetylase, Clr3, to repress pho1. This gene encodes a secreted acid phosphatase essential for phosphate acquisition in fission yeast. In the presence of phosphate, prt is produced from an upstream promoter and leads to silencing of pho1. Thus far, this has been explained by prt transcription leading to deposition of repressive methylation over the locus. However, this explanation is known to be incomplete since deletion of the only known histone methyltransferase does not lead to pho1 induction comparable to deletion of the prt promoter. This suggests that another mechanism must be involved in mediating transcriptional interference via non-coding transcription. In the present study the putative ncRNA-binding protein Seb1, together with the chromatin modifying complex SHREC, is demonstrated to associate with prt to elicit silencing of pho1 by a mechanism that is independent of H3K9 methylation and instead relies on deacetylase activity provided by the Clr3 component of SHREC. These data reveal a previously uncharacterised layer of ncRNA-mediated gene regulation and provide important conceptual advances in understanding the mechanisms governing the phenomenon known as transcriptional interference.